2014
DOI: 10.1016/j.jsbmb.2013.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Role of proinflammatory cytokines on expression of vitamin D metabolism and target genes in colon cancer cells

Abstract: Interleukin 6 (IL-6) and tumor necrosis factor alpha (TNFα) are proinflammatory cytokines that play a critical role in inflammatory bowel disease, as well as in colorectal tumorigenesis. We hypothesize that these cytokines modulate the expression and thus activity of the vitamin D system in colonic epithelial cells. We treated the colon cancer cell line COGA-1A for 6, 12, and 24 h with 1,25-dihydroxyvitamin D3 (1,25-D3), IL-6, TNFα, and with combinations of these compounds. Using quantitative RT-PCR, we analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
(37 reference statements)
5
33
0
Order By: Relevance
“…This might be attributed to CYP24A1 being increased in NSCLC tumors. Several studies have already examined the gain of 20q in gastro-esophageal junction [40], colon [41], breast [42], prostate [43], head and neck [44] as well as lung tumors [45,46]. Kong et al reported that CYP24A1 can reduce the 25(OH)D level and potentially increase NSCLC risk in cases with kinds of CYP24A1 polymorphisms [47].…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to CYP24A1 being increased in NSCLC tumors. Several studies have already examined the gain of 20q in gastro-esophageal junction [40], colon [41], breast [42], prostate [43], head and neck [44] as well as lung tumors [45,46]. Kong et al reported that CYP24A1 can reduce the 25(OH)D level and potentially increase NSCLC risk in cases with kinds of CYP24A1 polymorphisms [47].…”
Section: Discussionmentioning
confidence: 99%
“…The renal vitamin D-activating enzyme 1 α -hydroxylase (CYP27B1) is mainly regulated by serum PTH and FGF23, but extra renal production of 1,25(OH) 2 D by CYP247B1 is known to be induced by inflammatory cytokines such as TNF- α [36–39]. Further characterization of this novel component of vitamin D and inflammation will be important in future studies of vitamin D and inflammation in the elderly, especially in those with increased inflammatory disease activity such as RA patients [40].…”
Section: Discussionmentioning
confidence: 99%
“…It should be stressed however, that IL-6 and TNF-α, two pro-inflammatory cytokines that are crucial for development of inflammatory bowel disease and colorectal cancer, may impair the anti-inflammatory activity of vit. D [98] . The prospect that vit.…”
Section: α 25-dihydroxyvitamin D3mentioning
confidence: 99%